Optimizing Administration Services in Kasang Pudak Village: Analysis of Apparatus Capability, Digital Readiness, and Bureaucratic Culture - Dinda Rosanti Salsa Bela (Journal of Governance and Spatial Planning, 2026)
This study aims to analyze the quality of population administration services at the Kasang Pudak Village Office, Muaro Jambi Regency. As a village with rapid population growth, Kasang Pudak Village faces challenges in administrative service capacity and digitalization. This study uses a qualitative approach, data collection was conducted through direct observation, documentation studies, and in-depth interviews with village officials and community members selected purposively. Data analysis used the interactive model of Miles, Huberman, and Saldana. The results show that community satisfaction with the friendliness and speed of basic services is classified as very good. However, there are significant structural obstacles, namely: (1) low digital capabilities of the apparatus due to non-competent recruitment patterns, (2) the absence of formal published Standard Operating Procedures (SOPs), and (3) information technology infrastructure that is not yet systemically integrated. The existence of independent e-KTP recording facilities and a village website are important assets, but have not been balanced by integrated digital governance. The conclusion of this study is that service optimization requires a system integration model based on self-service applications, formalization of SOPs, and structured improvement of digital competencies of civil servants in order to transform services from a traditional-informal pattern to a modern, accountable bureaucracy